Unfolding health assessment case studies for the student nurse - Maynard, Kristi; Adimando, Andrea (Sigma Theta Tau International, 2020)
This book was designed with student nurses in mind. It is intended to serve as a tool to provide practice, enhance learning, and increase the propensity for retention and application of basic concepts of health and physical assessment. The book can be used by early-career nursing students who have just begun to cover its concepts as well as by pre-licensure exam students who may benefit from reiteration and reinforcement of concepts learned early on in nursing school and from practicing applying these concepts to more complex scenarios.Divided into 13 chapters, all of which are geared toward a particular subject matter. Chapters 1 and 2 introduce the concept of an unfolding case study and the nursing process. Chapter 3 provides an in-depth guide to answering NCLEX-style questions. There are several NCLEX-style questions broken down and analyzed within this chapter and several practice questions for your benefit. The remainder of the chapters are subject-based and cover assessment of the major body systems in a systematic and learner-friendly way. Readers will notice that while each chapter covers different content matter, the chapters are structured in similar ways so the reader can begin to develop a feel for and familiarity with an unfolding case study analysis.Goals for the book are:*Increased comfort level and confidence in analyzing patient scenarios in regards to basic health assessment *A more in-depth knowledge of basic health assessment concepts *Ample chances to practice applying concepts learned in your health assessment course to solidify the information you have learned*Increased confidence in answering NCLEX-style questions *Increased knowledge, skill levels, and confidence in assessing and managing patients with a variety of healthcare needsThe chapters of the book do not have to be completed in any particular order, as they are each individualized to certain subject matter categories. The authors recommend you use these unfolding case studies as a means of evaluating the ability to think critically and apply the concepts learned in health assessment classes to realistic patient scenarios. The book can be used as a study tool during health assessment classes, a health assessment refresher tool during other classes, and an NCLEX study tool after finishing nursing school.
Keywords: dept.nur

Moral distress in emergency and critical care nurses: A metaethnography - Arnold, Tracey C (Nursing Ethics, 2020)
Background:Moral distress has detrimental effects on nurses which impacts the entire healthcare cycle. Described as a crescendo effect, resolved situations of moral distress leave residue on the nurse with three potential outcomes: moral numbing, conscious objection to the situation, and burnout.Objective:This metaethnography strives to achieve a fuller understanding of moral distress by interpreting the body of qualitative work of moral distress in emergency and critical care nurses.Method:This study used the Noblit and Hare?s approach of interpretative synthesis. Ten studies met the criteria and were used in this synthesis.Ethical considerations:Ethical issues were minimal since no human subjects were involved. Ethical requirements were respected in all study phases.Results:The synthesis of qualitative research on moral distress resulted in one central theme, ?the battle within,? and five subthemes.Conclusions:The unique nature of this nursing specialty resulted in a lasting inner conflict for nurses that is consistent with the previously described crescendo effect. The effects are complex and long lasting and may potentially affect the nurses? future patient care.
17 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

An evolutionary concept analysis of secondary traumatic stress in nurses - Arnold, Tracey (Nursing Forum, 2020)
Purpose The purpose of this article is to provide conceptual clarification of secondary traumatic stress (STS) in nurses. Background As an empathetic helping profession, nurses are at increased risk for STS. Interchangeable usage of related terms among multidisciplinary literature has resulted in lack of conceptual clarity resulting in conflation of terms. Conceptual clarity is necessary for a foundation for further research on treatment. Methods Rodgers' evolutionary model of concept analysis. Results Nurses are predisposed to STS due to exposure, empathy, bonding, and personal factors. Essential attributes were found to be posttraumatic stress disorder-like symptoms, biological symptoms, social symptoms, and psychological symptoms. Resultant consequences included an altered worldview, interpersonal difficulties, and decreased occupational commitment. Conclusion This concept analysis, the first focusing on STS, provides conceptual clarity and a concept map of STS within the nursing population.
17 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/nuf.12409
Keywords: Rodgers' evolutionary model; concept analysis; concept map; dept.nur; peer-reviewed; secondary traumatic stress

Evaluation of an innovative curriculum enhancement: The conversation project - Pagano, Michael; Manger, Diana R.; O'Shea, Eileen; O'Sullivan, Cynthia (Nursing Education Perspectives, 2020)
Two northeast nursing schools piloted an innovative curriculum to teach The Conversation Project (TCP) to the next generation of nurses. The goal was to educate 26 graduate nursing students about how to have end-of-life and advance care planning conversations with people before they experience a crisis. The focus of assignments was on communicating newly learned TCP information. Postreflections demonstrated that participants felt their communication skills had been enhanced while their anxieties were reduced. The students' abilities to have end-of-life conversations increased. © Lippincott Williams & Wilkins.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85094221077
Keywords: Advance Care Planning; Communication; Conversation Project; Curriculum; End-of-Life Care; Graduate Nursing Education; Humans; Learning; Schools; Nursing; Students; Nursing; adult; advance care planning; anxiety; article; clinical article; communication skill; conversation; curriculum; dept.nur; female; graduate nursing student; human; interpersonal communication; learning; male; nursing education; nursing student; peer-reviewed

Reducing Student Nurse Stigmatization of the Patient Who Misuses Opioids A Scoping Review - Maynard, Kristi (Journal of Addictions Nursing, 2020)
The United States is in the midst of an opioid epidemic. The numbers of opioid-related deaths have been steadily climbing, magnifying the need for innovative intervention. Stigma is a set of preconceived, negative assumptions about a patient population or group. Stigma is a known deterrent to communication and the delivery of healthcare. Nurses serve as a primary contact for many marginalized patients within the healthcare system. The purpose of this scoping review is to gather known data on the use of educational interventions with nursing students to reduce stigmatizing tendencies. Inclusion criteria constituted an educational intervention involving student nurses and an effort to reduce stigmatizing attitudes toward patients who misuse opioids. The intervention must have taken place in an institute of higher learning between the years of 2003 and 2018. Exclusion criteria included community-wide studies. A single study was identified addressing nursing student reduction of stigmatization of the individual who uses opioids, and so, the search was expanded to include any student nursing intervention developed to reduce stigma toward any marginalized population. The following electronic databases were utilized in the search process: Cumulative Index of Nursing and Allied Health Literature, Google Scholar, Journal Storage, Microsoft Academic, and ScienceDirect. Reference pages of selected or related articles were reviewed in an attempt to identify additional pertinent literature through citation mapping. Fifteen studies were identified, each of which utilized a variable methodology for stigma reduction with varying levels of success. © Lippincott Williams & Wilkins.
3 citations (Crossref) [2023-10-31] WOS:000526707500008
Keywords: Attitude of Health Personnel; Clinical Competence; Humans; Opioid-Related Disorders; Social Stigma; Stereotyping; Students; Nursing; clinical competence; dept.nur; education; health personnel attitude; human; nurse; nursing student; opiate addiction; opioid misuse; peer-reviewed; psychology; social stigma; stereotyping; stigma; student

Equity, achievement, and thriving in nursing academic progression - Aragon, Sofia; Beauvais, Audrey M.; Friday, Vivienne; Green, Cheryl; Kiger, Anna J.; King, Simmy; Lear, Tina; Mahowald, Jane; McGuill, Gail; Perkins, Danielle; Valdez, Anna Maria; Velasco, Brian; et al. (Teaching and Learning in Nursing, 2020)
8 citations (Crossref) [2023-10-31] tex.ids: aragonEquityAchievementThriving2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088786114 type: Article
Keywords: dept.nur; equity; nursing education; peer-reviewed; progression

Nurses and Patients' Perspectives on Spiritual Health Assessment - Green, Cheryl (Journal of Religion & Health, 2020)
Nurses conduct physical and psychosocial assessments during admissions to healthcare facilities. Patients rely upon nurses to provide support and education during their journey, from periods of health decline to states of optimal wellness. Therefore, nurses are an ideal population to assess spiritual health. The value and necessity of spiritual assessment were explored on an inpatient unit providing medical and palliative care to patients. Two spiritual assessment tools, comprised each of five items, were evaluated by nursing staff and patients. Spiritual Assessment Tool 1 used language that was unaffiliated with religion, nor a belief in God, and Spiritual Assessment Tool 2 used language affiliated with faith and belief in God. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
2 citations (Crossref) [2023-10-31] WOS:000584350300004
Keywords: Attitude of Health Personnel; Humans; Nursing Staff; Palliative Care; Patients; Religion; Spirituality; adult; article; dept.nur; health personnel attitude; hospital patient; human; language; nursing staff; palliative therapy; patient; peer-reviewed; religion

Editorial for special collection: Current issues and practices in school nursing - Resha, Cheryl (SAGE Open Nursing, 2020)
1 citations (Crossref) [2023-10-31] tex.ids: reshaEditorialSpecialCollection2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082958509 type: Editorial
Keywords: dept.nur; peer-reviewed

Enough Is Enough: Confronting Workplace Bullying and Incivility - Green, Cheryl Ann (STTI, 2020)
tex.ids: greenEnoughEnoughConfronting2020
Keywords: dept.nur; ⛔ No DOI found

Challenging case in clinical practice: S-adenosyl methionine for mood support during corticosteroid therapy - Adimando, Andrea (Alternative and Complementary Therapies, 2020)
0 citations (Crossref) [2023-10-31] tex.ids: adimandoChallengingCaseClinical2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086454876 type: Article
Keywords: dept.nur

Equity and diversity in nursing education - Green, Cheryl (Teaching and Learning in Nursing, 2020)
Retention and development of ethnically diverse nursing students may be more likely to occur when nursing faculty receive training on factors that can impact academic success. By understanding complex school system dynamics in low-income areas, cultural, linguistic, gender, age, religion, and ethnic differences, students’ strengths can be readily recognized, embraced, and encouraged by nursing faculty. When the necessity of equity and diversity is recognized within nursing education, this may potentially translate to retention and completion of nursing programs by nursing students from diverse backgrounds, thereby increasing diversity within the nursing profession. © 2020 Organization for Associate Degree Nursing
14 citations (Crossref) [2023-10-31] tex.ids: greenEquityDiversityNursing2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089451312 type: Article
Keywords: Diversity; Equity; Nursing education; Nursing faculty; Nursing students; academic success; article; dept.nur; ethnic difference; female; gender; human; human experiment; lowest income group; male; nursing education; nursing student; occupation; peer-reviewed; religion

Should nursing be considered a STEM profession? - Green, Cheryl; John, Lori (Nursing Forum, 2020)
Background: The National Science and Technology Council developed a 5-year plan in 2013 to ensure that science, technology, engineering, and mathematics (STEM) experienced sustained growth within the United States (US). Nursing is comprised of multiple sciences that include chemistry, physics, biology, microbiology, anatomy and physiology, pharmacology, and the social and behavioral sciences of sociology, developmental lifespan psychology, and psychology. Science, technology, engineering, and math constitute the traditional STEM acronym. Nursing programs graduate nurses with both the rigorous academic coursework and diverse clinical skills necessary to provide patient care. These skills employed by nurses in the clinical setting can serve as the basis for the inclusion of the nursing profession as a STEM-designated profession by the federal government and educational institutions within the US. Problem: Currently, the US government does not acknowledge the profession of nursing as a STEM-designated profession. Acknowledgment of nursing as a STEM profession could potentially make more funding available for nursing education within the US and address nursing shortages both in clinical and academic settings. As well as position professional nurses for careers not only within the health sector but that of business and industry because of nurses’ STEM knowledge. Hence, enhancing the growth of STEM within the US and creating global market economic competitiveness with new innovation development. Approach: In the practice of nursing, nurses apply the sciences, math, and innovative technology in the assessments, diagnoses, and planning of patients’ care. Nurses implement scientifically-based interventions to treat illness and sustain human life and to ultimately evaluate the outcomes of the care provided to patients. Outcomes: Methodologies of evaluation of outcomes of patient care status post nursing interventions (ie, administration of intravenous antibiotics to treat pneumonia) are based upon rationales that have been derived from evidenced-based practice and nursing research; both originating from applied STEM knowledge. Conclusion: The formal designation by the US federal government, for nursing to be recognized as a STEM profession, can increase funding to the nursing profession and enhance the diversity of employment opportunities for nurses in industry and business. Thereby potentially decreasing nursing shortages and bringing national and worldwide recognition to nursing in both academia, industry, business, and clinical settings, as a profession contributing to the science of improvement of the health of all people through STEM knowledge. © 2019 The Authors. Nursing Forum published by Wiley Periodicals, Inc.
5 citations (Crossref) [2023-10-31] tex.ids: greenShouldNursingBe2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85076273828 type: Article
Keywords: Humans; Professional Role; STEAM; STEM; Science; classification; dept.nur; education; health care; human; inclusion; innovation; nursing; professional standard; science

Tick-borne illness - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Tracheostomy care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Trauma informed care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Varicella - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
4 citations (Crossref) [2023-10-31]
Keywords: Adaptation; Psychological; Adult; African American; African Americans; Aged; Aged; 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress; Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult

Autistic spectrum disorders - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Mental health - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Suicide - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Allergies - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorders - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Cardiac conditions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Depression - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Fractures - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Mosquito-borne disease - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Puncture wounds - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: skin and soft tissue infection (Boils, Cellulitis, Lymphangitis, and MRSA) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

Teaching accelerated nursing students’ self‐care: A pilot project - Green, Cheryl (Nursing Open, 2020)
Aim A benchmark of 4 has been determined for the reduction of self-reported stress by nursing students’ status post 5 weeks of holistic educational activities and interventions provided by a nurse educator. Design Provision 5 in the American Nurses Association Code of Ethics for Nurses with Interpretive Statements emphasizes the duty of the nurse to not only promote the health and safety of others, but to self as well (ANA, 2015, Code of ethics with interpretive statements, Nursebooks.org). A self-care for nurses’ pilot project was trialled with 25 accelerated nursing students over the course of 5 weeks. Holistic education programmes were facilitated by a nurse educator uninvolved in providing clinical or classroom education to the students. Methods The Standards for Quality Improvement Reporting Excellence (SQUIRE) guidelines are used in this pilot project as a framework to explore standardization of education of nursing students about self-care in nursing programmes and to promote positive health behaviours and student nurses’ insight into how nurses’ self-care can have an impact on patient outcomes. The self-care pilot project introduced the importance of self-care for the pre-licensure nursing student by teaching healthy eating, physical exercise, the value of sleep, use of positive affirmations and aromatherapy to a cohort of accelerated nursing students over the course of 5 weeks. The Star Model of Knowledge Transformation was the theoretical framework for the pilot study. Two questionnaires were used by the principal investigator to obtain participant data, the Project Participant Questionnaire and the Final-Year Group Questionnaire. Results On completion of the self-care for nurses’ pilot, the nursing students reported a reduction in stress and an increased ability to cope with stress after exposure to different holistic stress reduction strategies. An average benchmark of 4.36 was achieved indicating that the nursing students’ self-care had improved status post the interactive teaching intervention. Self-care taught to pre-licensure nursing students by nurse educators can enhance their self-awareness of the importance of stress reduction and care of themselves while enduring the academic rigour and simultaneous clinical practicum experiences in nursing programmes. Applying self-care behaviours to reduction of stress for nursing students may be of benefit to of students as they transition from the pre-licensure to graduate nurse roles. Hence, teaching health behaviours that are self-protective and contribute to maintaining safe clinical environments for nurses and the patients in their care.
10 citations (Crossref) [2023-10-31] tex.ids: greenTeachingAcceleratedNursing2019, lens.org/169-203-251-554-761
Keywords: dept.nur; nurse educators; nursing students; peer-reviewed; self-care; stress reduction